Unveiling associated factors related to congenital heart disease in children: A case-control study - Wijaya, Lisa Amelia; Yantie , Ni Putu Veny Kartika; Gunawijaya, Eka (Medical Faculty of Brawijaya University, Indonesia, 2025)
Background: Congenital heart diseases (CHDs) remain a significant global health burden and a leading cause of child mortality. However, limited evidence exists regarding the factors associated with CHDs, particularly in Indonesia. This study aims to identify factors associated with congenital heart defects (CHDs) in children. Methods: A case-control study was conducted using secondary data from pediatric cardiology patients at Ngoerah Hospital between 2021 and 2023, extracted from pedcardiobali.com. Patients aged 0–18 years who were diagnosed with CHD via echocardiography were included in the case group. Those with normal echocardiographic findings comprised the control group. Patients with incomplete medical records were excluded from the study. A total of 300 eligible subjects were selected, with 150 assigned to each group using a combination of purposive and random sampling methods. Multivariate logistic regression analysis was performed using SPSS version 29.0. Results: Among the 300 subjects, low birth weight (<2,500 grams) was significantly associated with CHDs (OR 3.365; 95% CI: 1.48–7.65; P = 0.004). Prematurity, maternal alcohol consumption, and congenital anomalies were identified as potential confounding factors (OR 1.19; 95% CI: 0.61–2.35; P = 0.61; OR 1.65; 95% CI: 0.45–6.06; P = 0.45; OR 1.98; 95% CI: 0.56–6.94; P = 0.29, respectively). No significant associations were found with maternal or paternal age, multiparity, multiple gestation, smoking, family history of CHDs, or maternal infection. Conclusion: Low birth weight is a dominant factor associated with CHDs. Early prenatal care and targeted interventions are crucial in reducing this risk. Further research is warranted to investigate the underlying mechanisms and genetic contributions to coronary heart disease (CHD).